The Effect of Celebrity Endorsement on Brand Image in Determining Purchase Intention - Adiba, Soraya Tsamara; Suroso, Agus; Afif, Nur Choirul (Journal of Accounting, Business and Management (JABM), 2020)
Smartphone becomes a standard platform for people to communicate with others.Nowadays, almost everyone has a smartphone because of its dependable functions.Therefore, the smartphone business is presently highly competitive, especially inIndonesia. One of the top smartphone brands in Indonesia is Oppo. To compete withother smartphone brands, Oppo uses celebrity endorsement as its marketing strategy.Oppo hires one of the eminent endorsers. This research purposes to investigate the effectof celebrity endorsement on brand image in determining purchase intention, using thecase of Oppo smartphone in Indonesia. This research uses a convenience samplingmethod utilizing 177 respondents who use Oppo smartphones and know Chelsea Islan.Data are analyzed using structural equational modeling (SEM) and AMOS statisticalsoftware. The results of hypothesis testing on this study shows that celebrity expertise,celebrity attractiveness, and celebrity trustworthiness have a positive effect on brandimage. On the other hand, celebrity match-up has a negative effect on brand image.Finally, brand image has a positive effect on purchase intention